Sustainable utilization of agro-industrial fruit and vegetable waste in industry: potential to produce bioactives and biomaterials: Aprovechamiento sostenible de residuos agroindustriales de frutas y vegetales en la industria: potencial para producir bioactivos y biomateriales - Enriquez-Estrella, Miguel; Arboleda-Alvarez, Luis; Ricaurte-Órtiz, Paul; El Salous, Ahmed; Andrade-Alban, Maria- José (Revista Colombiana de Ciencias Pecuarias, 2025)
Sustainable utilization of agro-industrial waste has been established as a key strategy for addressing environmental and economic challenges. This study focused on identifying how agro-industrial waste from fruits and vegetables is utilized globally. To achieve this, the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method was employed, which facilitates the conduct of systematic reviews and meta-analyses. This approach allows for a comprehensive and structured literature search, ensuring transparency and reproducibility in the review process. The study’s results revealed that 29.9% of the waste is optimized through fermentation processes, while 16% is utilized via supercritical fluid extraction (SFE). These findings conclude that sustainable utilization of agro-industrial waste, through innovative methods such as fermentation and supercritical fluid extraction, provides effective solutions to environmental and economic challenges. These methods not only enable the conversion of waste into high-value products but also contribute to waste reduction and the promotion of a circular economy, aligning with global goals of waste reduction and resource optimization.